Theological Pretext for Slavic War and Third Reich: A Literature Study for Church’s Reflection - Daniel Trihandarkha (Predica Verbum: Jurnal Teologi dan Misi, 2022)
The ambition of one man, namely Adolf Hitler, to initiating the massacre of the whole population of Jewish in Europe needed a pretext. In the age where the liberal thinkers and rationalist theology were wanning there had not been, seemingly, another way to mobilize the whole army of the disappointed German nationalist who lost their pride in WWI, rather than the religious narrative of the reestablishment of the Kingdom of God through the Aryan. Whether the pretext justified the massacre theologically, or the ambition served the theology coherently in praxis, is still debatable in nature. This writing will examine the formulation of theology of German church supporting the Hitler’s Third Reich, and other religio-political driven narrative in Europe, especially in Slavic nations. Finally, throughout multi political changes which happened in Indonesia in the last 300 years, what can churches do to avoid such a despicable move in relation to the government.